ACTIVE, BELIEF, AND CONSEQUENCE (ABC) MODEL TECHNIQUE IN MINIMIZING STUDENTS’ SPEECH ANXIETY - Syafryadin Syafryadin; Nurkamto, J, Linggar, D. A; Mujiyanto, J (Universitas Negeri Padang, 2017)
Speech anxiety becomes one of the obstacles for the students to enhance their speaking competence. The students felt afraid of speaking in public because the students were apprehansion to make mistakes, gain negative evaluation and less preparation in giving speech. Thus, this study was designed to investigate whether Speech Training with ABC Model Technique could reduce the students’ speech anxiety or not. This study used an experimental research. The population of this study is all fourth semester students in the English Department in of universities in Kendari at academic year of 2015/2016. The instruments of this study were anxiety test, observation checklist, interview guidline and note taking. The data were analyzed quantitatively and qualitatively. The quantitative data were analyzed by SPSS 22` The finding of this study was ABC Model Technique could reduce the reduce the students’ speech anxiety. It was proved by the mean score of the students for pretest and posttest. The mean score of the pretest was 104.22 and the posttest was 91.50. It means that most of the students got low anxiety level. Therefore, ABC Model Technique reduced the students’ speech anxiety.